(untitled) (Research, Society and Development, 2021)
Sodium is a very useful mineral and known in the kitchens of homes and restaurants around the world as salt, but its importance is not attributed only to the flavor it brings to food. This micronutrient, also known as a type of electrolyte, is essential for maintaining the functionality of the human body. There is a risk to the health of individuals when their levels in the body are inadequate. This study aimed to analyze the importance of knowledge and correct diagnosis of health professionals to provide optimal treatment for hospitalized patients. This is a cross-sectional and descriptive study, with qualitative and quantitative data, with a snowball methodology, where it was publicized on social media and so one candidate could invite another to respond to the survey. Data collection was carried out through the application of an online questionnaire (Google Forms), in order to try to understand and ascertain the knowledge of professionals working in Intensive Care Units (ICUs) regarding the diagnoses and behaviors when receiving patients with critical levels of sodium. The results obtained showed that there is little experience of time in the ICU, for a large portion of the sample, and that most hospitalized patients present a picture of hyponatremia. In addition, the most frequent diagnosis is made through laboratory analysis, where the recurrent approach is the administration of fluid volume. It is necessary to expand diagnostic strategies to implement adequate treatment procedures.